INSTRUMENTS FOR EVALUATING INCLUSIVE PRACTICES, CULTURES AND POLICIES IN UNIVERSITY CONTEXTS - Andrade Louzada, Juliana Cavalcante de [UNESP]; Oliveira Martins, Sandra Eli Sartoreto de [UNESP] (Univ Estadual Paulista-unesp, Fac Ciencias Letras Assis, 2022)
The presence of people with disabilities in higher education shows affirmative policies in defense of a university accessible for all. It also calls on distinguished members of the academic community to reduce inequalities in access and participation in Higher Education, to population groups in a situation of social, economic, and educational vulnerability, including people with disabilities. This research describes the preparation of the instrument to identify inclusive policies, cultures, and practices in university contexts. It is the Inclusion Index for Higher Education (INES), translated and adapted for use in different university socio-educational environments. The results indicated adjustments in the original instrument and created the adapted version to the Brazilian university context. Its applicability reaffirms the institutional commitment of the academic community for a social, critical, and transforming perspective of the training processes in Higher Education
Keywords: Accessibility; Inclusive education; Higher education; Inclusion